Microbial characterisation of the edible grasshopper Ruspolia differens in raw condition after wild-harvesting in Uganda. (February 2019) - Ssepuuya, Geoffrey; Wynants, Enya; Verreth, Christel; Crauwels, Sam; Lievens, Bart; Claes, Johan; Nakimbugwe, Dorothy; Van Campenhout, Leen
Abstract: This research aimed at establishing the chemical intrinsic properties and the microbial quality of an edible grasshopper Ruspolia differens and the effect of its source (geographical area) in Uganda, trading point, swarming season and plucking on these parameters. The intrinsic properties of the grasshopper can support the growth of a wide variety of microorganisms. High counts of total aerobic microbes, Enterobacteriaceae, lactic acid bacteria, total aerobic spores, and yeasts and moulds were obtained. Metagenetic analyses yielded 1793 Operational Taxonomic Units (OTUs) belonging to 24 phyla. Actinobacteria, Bacteroidetes, Firmicutes, Fusobacteria and Proteobacteria were the most abundant phyla, while members of the genera Acinetobacter, Buttiauxella, Lactococcus, Staphylococcus and Undibacterium were the most abundant OTUs. A number of genera harbouring potential pathogens ( Acinetobacter, Bacillus, Buttiauxella, Campylobacter, Clostridium, Staphylococcus, Pseudomonas and Neisseria ) were identified. The geographical area, trading point, swarming season and plucking significantly influenced microbial counts and bacterial diversity. The high microbial counts predispose R. differens to fast microbial spoilage, while the presence of Clostridium and Campylobacter makes this grasshopper a potential source of food borne diseases. Further research should identify the specific spoilage microorganisms of R. differens and assess the characteristics of this grasshopper that support growth of food pathogens. Highlights: The pH, aw and moisture content of R. differens reliably support microbial growth. The high microbial counts predispose R. differens to fast spoilage. Metagenetics yielded 1793 Operational Taxonomic Units (OTUs) belonging to 24 phyla. Geographical area of source, season and plucking influenced bacterial diversity. R. differens potentially harbours human pathogenic bacteria.